Fate of 15N-labelled ammonium nitrate with or without the new nitrification inhibitor DMPSA in an irrigated maize crop. (January 2018) - Guardia, Guillermo; Vallejo, Antonio; Cardenas, Laura M.; Dixon, Elizabeth R.; García-Marco, Sonia
Abstract: Nitrification inhibitors, originally proposed for nitrate leaching mitigation, are recommended as effective nitrous oxide (N2 O) mitigation strategies. Several compounds have been trialled and used in the past including dicyandiamide (DCD) or 3, 4-dimethylpyrazole phosphate (DMPP). Yet, little is known about the new nitrification inhibitor 2-(3, 4-dimethyl-1H-pyrazol-1-yl) succinic acid isomeric mixture (DMPSA). A field experiment using 15 N single-labelled ammonium nitrate ( 15 NH4 NO3 or NH4 15 NO3 ) was conducted to understand the effectiveness of DMPSA on a biochemical basis in an irrigated maize ( Zea mays L.) crop. Gaseous fluxes, i.e. N2 O, 15 N2 O, 15 N2, methane (CH4 ), and carbon dioxide (CO2 ) were measured, as well as soil mineral N, yield components and 15 N recovery in plant and soil. During the maize cropping period, the use of DMPSA significantly reduced cumulative N2 O emissions (118 g N ha −1 ) compared to ammonium nitrate without inhibitor (231 g N ha −1 ). The 15 N analyses revealed that most N2 O losses (particularly during the emission peak) came from 15 NH4 NO3 (i.e. nitrification, nitrifier denitrification and/or coupled nitrification denitrification) rather than NH4 15 NO3 in this calcareous low C-content soil. As expected, DMPSA decreased N2 O losses from 15 NH4 + oxidation, but an effect on non-target microorganisms was noticed, as shown by the significant reduction of respiration rates and N2 O losses coming from 15 NO3 − . No significant effect of DMPSA on CH4 oxidation or 15 N2 fluxes was observed. The DMPSA did not lead to a significant improvement of the dry weights of grain or biomass, although an increment of root biomass by 64% was found. This compound also tended to increase plant N recovery (average 67.8%) and to decrease soil N recovery (average 18.3%) but differences were not statistically significant. Conversely, the nitrification inhibitor significantly reduced the residual fertilizer-N in the 15–30 cm and 30–45 cm soil layers. The use of DMPSA was confirmed as a highly effective tool to reduce N2 O emissions from irrigated crops in semi-arid areas. Highlights: The new inhibitor DMPSA reduced cumulative N2 O losses by 49% with no effect on CH4 sink. DMPSA decreased N2 O losses from NH4 + oxidation and also from denitrification of NO3 − The DMPSA did not show any significant effect on yields or the fertilizer-N recovery in plant and soil. The use of NO3 − -based fertilizers or DMPSA with NH4 + -based fertilizers can reduce N2 O losses in irrigated agro-ecosystems.